PREDIKSI EROSI DAN SEDIMENTASI PADA BERBAGAI PENGGUNAAN LAHAN DI SUB DAS DANAU LIMAU MANIS PADA DAS KURANJI KOTA PADANG - Aprisal Aprisal; Junaidi Junaidi (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
Erosion prediction and sedimentation measurement in sub-watershed Danau Limau Manis was conducted to predict erosion and sedimentation from several land uses there, as well as to find out other types of land use being able to reduce erosion as tolerated one. Methods used for this research was divided into 1) soil map analyses(topography and land use), rainfall data, (2) survey and soil sampling in the field, (3) soil analyses in laboratory, and (4) data analyses using erosion model “USLE” and “Sediment Delivery Ratio”. The results showed that there 4 types of land use (mixed garden, settlement, farming, and bush) having erosion higher than tolerated erosion(etol). This was due to low plant density and many areas open, therefore, rainfall will directly struck soil aggregates causing dispersion. To eliminate or reduce the erosion rate into etol could be done by “agroecotechnology conservation”method. That is by increasing plant density, changing bush land into garden so that the crop coefficient will became 0.001. While at settlement area, it should be planted by perennial trees, built terrace and water ditch. Garden and bush land contributed highest amount of sediment, however it can be reduced if agroecotechnology conservation method is applied.Key word: watershed, erosion, sedimentation",